2016
DOI: 10.1007/s11869-016-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic study of a mixture of magnetite and metallic iron in indoor dust samples

Abstract: Magnetite in mixture with metallic iron in indoor dust samples was examined using several magnetic analyses, thermomagnetic curves of the magnetic susceptibility and the induced magnetization vs. temperature, hysteresis loops, and first-order reversal curves. The study of the magnetic properties was supplemented by the analysis of chemical elements and electron microscopic observation. The metallic iron in the mixture affects the values of hysteresis parameters, decreasing coercivity (B c) and increasing satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The mean I/O for EC for both sampled season periods equals 0.6 in both schools, similar to the one obtained from total magnetic PM measured on bio‐sensors (0.6 and 0.9, respectively for School 1 and 2). The magnetic fraction of PM found indoors also points to external sources, hence traffic sources, in agreement with previous studies that found that magnetic particles on household dust are derived from traffic and industrial activities (Beata Górka‐Kostrubiec & Iga Szczepaniak‐Wnuk, 2017 ; Jelenska et al., 2017 ; Kelepertzis et al., 2019 ). Other known potential sources of magnetic PM indoors are cooking, combustion processes, smoking (Jordanova et al., 2006 ) and laser printing (ink composed of nanoparticles, Pirela et al., 2015 ), all of which are absent in the studied schools.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean I/O for EC for both sampled season periods equals 0.6 in both schools, similar to the one obtained from total magnetic PM measured on bio‐sensors (0.6 and 0.9, respectively for School 1 and 2). The magnetic fraction of PM found indoors also points to external sources, hence traffic sources, in agreement with previous studies that found that magnetic particles on household dust are derived from traffic and industrial activities (Beata Górka‐Kostrubiec & Iga Szczepaniak‐Wnuk, 2017 ; Jelenska et al., 2017 ; Kelepertzis et al., 2019 ). Other known potential sources of magnetic PM indoors are cooking, combustion processes, smoking (Jordanova et al., 2006 ) and laser printing (ink composed of nanoparticles, Pirela et al., 2015 ), all of which are absent in the studied schools.…”
Section: Discussionsupporting
confidence: 90%
“…( 2009 ) and Sagnotti and Winkler ( 2012 ) from exhaust residues from gasoline and diesel motors as well from brake wear dust collected directly in situ. This could result from different sources of particles, meaning different magnetic mineralogy such as high coercivity minerals like hematite(of geological origin e.g.,) or metallic iron (linked to abrasion of combustion cylinder, pads and disk brakes), which influences SIRM and coercivity values (Gorka‐Kostrubiec & Szczepaniak, 2017 ; Gorka‐Kostrubiec et al., 2019 ) and therefore impact the S‐Ratio and/or grain sizes parameters.…”
Section: Resultsmentioning
confidence: 99%
“…S1 d-f) further confirm metallic Fe particles in the household dust, which is consistent with the thermomagnetic results. These metallic Fe particles are irregular sheetlike or blocky and reported by other studies (Zhang, 2011;Moreno et al, 2015;Gόrka-Kostrubiec et al, 2015;Jeleńska et al, 2017;Gόrka-Kostrubiec and Szczepaniak, 2017). Jeleńska et al, (2017) found angular, metallic Fe particles in office dust in Warsaw (Poland) and considered that these particles were possibly generated by the abrasion of vehicle suspension components.…”
Section: J O U R N a L P R E -P R O O F 42 Identification Of Sources ...mentioning
confidence: 59%
“…Meanwhile, a continuous decrease of magnetic susceptibility up to 700 • C for sample 19 can be observed, suggesting the presence of a high-temperature magnetic phase. According to previous studies on the magnetic mineralogy of street dust from Warsaw [27,28], this tail on the curve of κ(T) between 600 and 700 • C indicates the presence of metallic iron, which exhibits a Curie temperature of 780 • C [50,[60][61][62]. The heating curve of κ(T) for sample 32 does not show metallic Fe as the value of κ above the T C for magnetite is almost zero.…”
Section: Identification Of Magnetic Minerals In Topsoil Polluted By Technogenic Particles Emitted By the Ironworkmentioning
confidence: 92%